PENYELESAIAN SENGKETA AKIBAT WANPRESTASI PIHAK PENYEDIA BARANG DAN JASA MELALUI ELEKTRONIK KEPADA PEMERINTAH PERSFEKTIF PERATURAN PRESIDEN NOMOR 16 TAHUN 2018 TENTANG PENGADAAN BARANG/JASA PEMERINTAH - Siregar, Muhammad Ikhsan; Mukidi, Mukidi; Affan, Ibnu (LPPM YPITI, 2021)
The procurement of goods/services is funded from the State/Regional Revenue and Expenditure Budget (APBN/APBD), and generally always increases from year to year. Likewise, the components of APBN/APBD expenditure in the form of capital expenditure (investment)/direct expenditure, the implementation of which is carried out through the procurement of goods/services. The formulation of the problem in this thesis is how to procure government goods/services through electronic procurement services to the government, how to resolve disputes due to default on government procurement of goods/services through electronic procurement services to the government, how legal solutions are carried out in government procurement of goods/services. through electronic services. The research method used is descriptive analysis that leads to normative juridical legal research, namely research conducted by referring to legal norms, namely researching library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results show that the procedure for procuring government goods/services through the government electronic procurement services is regulated in Presidential Regulation Number 12 of 2021 concerning Amendments to Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods/Services which has been fully and in sufficient detail in the process. government procurement of goods/services. Settlement of disputes due to default on government procurement of goods/services through electronic procurement services to the government, namely if the parties commit acts that are not in accordance with the provisions for procurement of goods and services based on Presidential Regulation Number 12 of 2021 concerning Amendments to Presidential Regulation Number 16 of 2018 concerning Procurement of Goods/ Government services, will be subject to sanctions in the form of administrative sanctions, sued for compensation / being sued in a civil manner.